Society perception About Pascas Government Role Sag At Stone Rotten sub-district Bounces Up Pauhs district Hill Padang City - Gempani, Gempani; Rianto, Slamet; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
This research intent to get data and information about Pascas Government Role Sag At Stone Rotten sub-district Bounces Up Pauhs district Hill Padang City. Pascas Commanding role Sag is seen from medium repair facet and prasarana generically, home remedial help application society and protection to disasters vulnerable group. This observational type is descriptive. Observational population is patriarch that strikes sag at stone rotten sub-district Bounces Up Hill that total 199 patriarches. Respondent sample to be taken ala proportional random sampling as much 50% so total respondent samples 100 patriarches. Observational yielding data at o by use of descriptive statistic with percentage formula. There is result even of Society Perception research About Pascas Government Role Sag At Stone Rotten sub-district Bounces Up Pauhs district Hill Padang City is (1 ) Local government has fixed medium and prasarana generically which strikes this disaster gets to be seen that in a general way society which answer downed bridge was fixed by government as much 100 person (100%) (2 ) Local government has given home repair help society which strikes this disaster gets to be seen that in a general way society answers have available home remedial help of commanding 100 person (100%) (3 ) Local government has given vulnerable group protection this disaster gets to be seen that government has given tofu on that region society is vulnerable act of god